Uwarunkowania realizacyjne projektów Unii Europejskiej wspomagających kształcenie na kierunku Informatyka Ekonomiczna - Łosiewicz, Ewa; Nowicki, Adam; Owoc, Mieczysław L. (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Education oriented on business informatics seems to be one of the more attractive as well as rather difficult fiellds studies. Joining the UE education systems in Poland should be transformed to fulfil signed agreemented (the Bologna process and the Lisbon strategy) and to create conditions for making studying more flexible and mobile. The crucial aim of the paper is a presentation of critical factors that may impact projects relevant to this area. All these factors have been divided onto two groups: these can be treated as advantages and these, which are real limits. For example: ways of financing, education standards in particular EU countries and technological infrastructure existing in university campuses. Two project undergoing in the 6'h Framework (the Socrates preogramme) have been taking into account: European University Lifelong Learning Network and BIN-Net: Business Informactics Network in Common Europe. The author's ezperiences allowed them to create definition and context presentation of the mentioned factors. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 186-193